Predictors of self-injurious behaviour exhibited by individuals with autism spectrum disorder. - Richman, D. M.; Barnard-Brak, L.; Bosch, A.; Thompson, S.; Grubb, L.; Abby, L. (Journal of Intellectual Disability Research, 2013)
Background Presence of an autism spectrum disorder is a risk factor for development of self-injurious behaviour ( SIB) exhibited by individuals with developmental disorders. The most salient SIB risk factors historically studied within developmental disorders are level of intellectual disability, communication deficits and presence of specific genetic disorders. Recent SIB research has expanded the search for risk factors to include less commonly studied variables for people with developmental disorders: negative affect, hyperactivity and impulsivity. Method A heterogeneous sample of 617 individuals with autism spectrum disorder diagnoses was derived from the National Database of Autism Research. Latent constructs were estimated from items of the community version of the Aberrant Behaviour Checklist. Structural equation modelling was used to assess whether impulsivity, hyperactivity, negative affect, severity of stereotypy, intellectual functioning or severity of autism symptoms predicted severity of SIB. Results Impulsivity (β = 0.46), followed by intellectual functioning (β = −0.39), and stereotypy (β = 0.23) were the variables most highly predictive of increased SIB; impulsivity and stereotypy remained significant predictors of SIB after severity of autism symptoms and intelligence quotient ( IQ) were controlled for. Conclusions High levels of impulsivity and stereotypy were significant predictors of SIB in a large and diverse sample of people with confirmed autism diagnoses. Future research is needed on the effects of reducing impulsivity and stereotypy on the outcomes of treatment, early intervention and attempts to prevent the development of SIB.